Relevansi Filsafat Hukum dalam Pemahaman Konsep Keadilan - Alon Maemanah; Bunga Kinasih; Dominikus Rato; Fendi Setyawan (As-Syar'i: Jurnal Bimbingan & Konseling Keluarga, 2024)
Justice according to legal philosophy considers every aspect related to the terminology of legal philosophy and justice, which is the purpose and ideal of law and covers the entire nature of the concept of justice that wants to be upheld by the existence of law. Based on the arguments of Plato who is used as a reference for justice, Thomas Aquinas who states that Justice is a proportional equality, and John Rawles who has a perspective that justice is fairness so that the value of justice studied by the philosophy of law will find the answer based on the philosophy of law itself. Justice is one of the important elements for human life so that there is a balance of rights and obligations to achieve the truth. It also explains that between duty and truth must be in harmony and achieve balance. Law is only a set of formulas when the law has not been able to establish justice and when the law is far from justice, the law will lose its meaning. Legal formulation is the harmony and harmony of legal proportionality and also legal certainty.